Amount of Stimulation Received at Home and Growth During Infancy Have Positive Association With Psychomotor Development of Poor Urban Bangladeshi Infants (Journal of Chittagong Medical College Teachers' Association, 2012)
Biological and psychosocial factors along with cumulative environmental factor have effect on the later childhood development. The detrimental effect of these factors on development varies from studies to studies in different geographical regions with variation in the causality. LBW (Low birth weight) children (birth weight